Relationship between BMI and risk of impaired glucose tolerance and impaired fasting glucose in Chinese adults: a prospective study - Xin Zhang; Yankun Yue; Shaobo Liu; Xiangfeng Cong; Wenjuan Wang; Jianhong Li (BMC, 2023)
Abstract Background Current studies in most Western countries have largely focused on body mass index (BMI) as an important risk factor for impaired glucose tolerance (IGT) and impaired fasting glucose (IFG), which have different pathophysiological bases. In people with obesity, the prevalence of IGT is higher and the prevalence of IFG is lower. The prevalence of IGT in the Asian population is higher than that in the white population, and the obesity rate in China is still increasing. However, few cohort studies explore the relationship between BMI and the incidence of IGT and IFG in China. We aimed to explore the relationship between BMI and the risk of IGT and IFG in Chinese adults and analyze the differences between them. Methods The baseline data were obtained from the 2010 China Chronic Disease and Risk Factor Surveillance, of which 20 surveillance sites were followed up from 2016 to 2017. Finally, in this study, a total of 5,578 studies were grouped into BMI categories of underweight (BMI < 18.5 kg/m2), normal weight (18.5-23.9 kg/m2), overweight (24.0-27.9 kg/m2), and obesity (≥ 28.0 kg/m2). We used the unconditional logistic regression model to analyze the relationship between BMI and the risk of IGT and IFG. Results During an average follow-up of 6.4 years, 562 developed IGT and 257 developed IFG. After age, gender, urban and rural areas, physical activity, family history of diabetes, hypertension, abdominal obesity, dyslipidemia, and other factors were adjusted, overweight increased the risk of IGT by 35% [odds ratio (OR) 1.35, 95% confidence interval (CI) 1.08-1.70], and obesity increased the risk of IGT by 77% (OR 1.77, 95% CI 1.27-1.47). After the factors consistent with the above were adjusted, only obesity increased the risk of IFG by 122% (OR 2.22, 95% CI 1.39-3.54). Conclusions In China, obesity is an important risk factor for IGT and IFG, and the risk of IGT increases during the overweight stage.